Disnarration and the Unmentioned in Fact and Fiction - Lambrou, Marina; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2019)
'Disnarration and the Unmentioned in Fact and Fiction is a lucid, rich, and insightful contribution to narrative poetics. It illuminates the functioning of factual and fictional storytelling.' -Gerald Prince, Professor of Romance Languages, University of Pennsylvania, USA and author of A Dictionary of Narratology In this book Marina Lambrou explores the dimension of narrative storytelling described as 'the disnarrated' - events that do not happen but which are referred to - across three genres of texts: personal narratives; news stories; and fiction (literary and film). The book begins by asking why such disnarrated narratives are nevertheless considered tellable. It moves on to examine the pervasiveness of this phenomenon in news reports about "near misses" and the shared personal narratives about dangerous experiences, where "truth" is expected to be central their telling. It further discusses how disnarration is generatedin counterfactual "what if?" scenarios in fiction where characters follow alternative, forked paths with fascinating unexpected consequences. This engaging work offers original insights to anyone interested in storytelling and will appeal in particular to scholars of language and literature, stylistics, narratology, media, film and journalism. Marina Lambrou is Associate Professor in English Language and Linguistics at Kingston University, UK. She has published on a variety of language-related themes that include personal and trauma narratives, stylistics, media discourses and narratology across factual and fictional texts. She is the current Chair of the Poetics and Linguistics Association (PALA).
Chapter 1: Introduction to disnarration and the unmentioned in fact and fiction -- Chapter 2: Telling stories -- Chapter 3: Disnarration and the unmentioned in fact: oral narratives of personal experience -- Chapter 4: Disnarration and the unmentioned in fact: news stories -- Chapter 5: Disnarration and the unmentioned in fiction -- Chapter 6: Conclusion.
Keywords: Language and languages -- Style; Fiction; Communication; Culture -- Study and teaching; Stylistics; Fiction Literature; Media and Communication; Cultural Studies